Colon Cancer and Diagnosis Stage - Duha Thamer Abbas Kazem; Taiba Ali Hussein Abdullah; Hind Khudair Rahim Matar; Alia Hussein Jabr Ibrahim (Genius Journals, 2024)
Colorectal cancer grows slowly and does not cause symptoms for a long time. Symptoms depend on the type and location of the cancer and its grade Fatigue and weakness caused by occult bleeding (bleeding that is not visible to the naked eye) may be a person's only symptoms.A tumor in the left (descending) colon is likely to lead to obstruction at an early stage, because the diameter of the left colon is small, and the stool is semi-solid. A person may seek medical treatment because of abdominal cramps, severe pain, or constipation A tumor in the right (ascending) colon does not lead to obstruction until a later stage of the cancer, because the diameter of the ascending colon is larger, and the contents that pass through it are in the form of a liquid, so the tumor in the right colon when discovered may be larger than the tumor in the left colon.Most colon cancers cause bleeding, usually slowly. The stool may have traces of blood or be mixed with blood, but blood often cannot be seen. Bleeding during bowel movements is the most common first symptom of rectal cancer. Doctors should consider the possibility of a diagnosis of colon cancer. Cancer whenever they find bleeding in the rectum, even if it is clear that the person has hemorrhoids or diverticular disease. Pain during bowel movements and a feeling that the rectum has not completely emptied are other symptoms of rectal cancer. Sitting may also be painful, but the person does not feel pain. Usually from the cancer itself unless it has spread to tissue outside the rectum
Keywords: Diagnosis Stage; Colon Cancer; bleeding